Fatal Case of Probable Invasive Aspergillosis after Five Years of Heart Transplant: A Case Report and Review of the Literature - Toufik Mahfood Haddad; Mahesh Anantha Narayanan; Krista E. Shaw; Renuga Vivekanandan (Case Reports in Infectious Diseases)
Invasive fungal infections are very common in solid organ transplants and occur most frequently in the first three months after transplant. A 49-year-old female with a history of two remote heart transplants with the most recent one occurring 5 years ago was admitted for increasing shortness of breath, cough, and fever. Computerized tomography (CT) scan of the chest showed left lower lung ground-glass and tree-in-bud opacities. She was started on broad spectrum antibiotics along with ganciclovir and micafungin. Ganciclovir was added due to the patient’s past history of CMV infection and empiric fungal coverage with micafungin. Bronchoalveolar lavage (BAL) was performed as her respiratory status worsened and voriconazole was added for possible aspergillosis in combination therapy with micafungin. BAL galactomannan returned positive which was suggestive of aspergillosis. Patient worsened clinically and subsequently succumbed to cardiorespiratory arrest despite our best efforts. It is important to have a high degree of clinical suspicion for invasive aspergillosis in transplant patients even many years after transplant and initiate aggressive therapy due to poor outcomes.